B7-H3 Negatively Modulates CTL-Mediated Cancer Immunity - Yonesaka, Kimio; Haratani, Koji; Takamura, Shiki; Sakai, Hitomi; Kato, Ryoji; Takegawa, Naoki; Takahama, Takayuki; Tanaka, Kaoru; Hayashi, Hidetoshi; Takeda, Masayuki; Kato, Sigeki; Maenishi, Osamu; et al. (Clinical cancer research, 2018)
Purpose: Anti-programmed-death-1 (PD-1) immunotherapy improves survival in non–small cell lung cancer (NSCLC), but some cases are refractory to treatment, thereby requiring alternative strategies. B7-H3, an immune-checkpoint molecule, is expressed in various malignancies. To our knowledge, this study is the first to evaluate B7-H3 expression in NSCLCs treated with anti-PD-1 therapy and the therapeutic potential of a combination of anti-PD-1 therapy and B7-H3 targeting. Experimental Design: B7-H3 expression was evaluated immunohistochemically in patients with NSCLC (n = 82), and its relationship with responsiveness to anti-PD-1 therapy and CD8+ tumor-infiltrating lymphocytes (TILs) was analyzed. The antitumor efficacy of dual anti-B7-H3 and anti-programmed death ligand-1 (PD-L1) antibody therapy was evaluated using a syngeneic murine cancer model. T-cell numbers and functions were analyzed by flow cytometry. Results: B7-H3 expression was evident in 74% of NSCLCs and was correlated critically with nonresponsiveness to anti-PD-1 immunotherapy. A small number of CD8+ TILs was observed as a subpopulation with PD-L1 tumor proportion score less than 50%, whereas CD8+ TILs were still abundant in tumors not expressing B7-H3. Anti-B7-H3 blockade showed antitumor efficacy accompanied with an increased number of CD8+ TILs and recovery of effector function. CD8+ T-cell depletion negated antitumor efficacy induced by B7-H3 blockade, indicating that improved antitumor immunity is mediated by CD8+ T cells. Compared with a single blocking antibody, dual blockade of B7-H3 and PD-L1 enhanced the antitumor reaction. Conclusions: B7-H3 expressed on tumor cells potentially circumvents CD8+-T-cell–mediated immune surveillance. Anti-B7-H3 immunotherapy combined with anti-PD-1/PD-L1 antibody therapy is a promising approach for B7-H3–expressing NSCLCs. Clin Cancer Res; 24(11); 2653–64. ©2018 AACR.